Enhanced Photocatalytic Properties of ZnO Nanoparticles for the Degradation of Rhodamine B - Janjua, S. I.; Hussain, M.; Ahmad, M.; Shahzada, S.; Ali, G.; Maaz, K.; Karim, S. (The Nucleus, 2015)
This study investigates the photocatalytic properties of hydrothermally synthesized ZnO nanoparticles for the degradation of RhB. The structural and morphological properties of the product have been characterized by XRD, EDS, SEM and TEM. Structural measurements reveal that single crystalline nanoparticles in the range of 9 to 130 nm are formed. The elemental composition is analyzed by EDX. The photocatalytic properties demonstrate that the ZnO nanoparticles stand an active photocatalyst which completely degrade RhB in 30 min. Therefore ZnO nanoparticles may have significant implications for degradation of organic contaminants and for the environment remediation.